Preventing preterm birth with progesterone: costs and effects of screening low risk women with a singleton pregnancy for short cervical length, the Triple P study - Duvekot Johannes J; Sikkema Marko J; Bilardo Katia M; Oudijk Martijn A; Woiski Mallory; Willekes Christine; Bloemenkamp Kitty WM; Bossuyt Patrick M; Porath Martina; van Wassenaer Aleid; de Miranda Esteriek; Pajkrt Eva; et al. (BMC, 2011)
Abstract Background Women with a short cervical length in mid-trimester pregnancy have a higher risk of preterm birth and therefore a higher rate of neonatal mortality and morbidity. Progesterone can potentially decrease the number of preterm births and lower neonatal mortality and morbidity. Previous studies showed good results of progesterone in women with either a history of preterm birth or a short cervix. However, it is unknown whether screening for a short cervix and subsequent treatment in mid trimester pregnancy is effective in low risk women. Methods/Design We plan a combined screen and treat study among women with a singleton pregnancy without a previous preterm birth. In these women, we will measure cervical length at the standard anomaly scan performed between 18 and 22 weeks. Women with cervical length ≤ 30 mm at two independent measurements will be randomly allocated to receive either vaginal progesterone tablets or placebo between 22 and 34 weeks. The primary outcome of this trial is adverse neonatal condition, defined as a composite outcome of neonatal mortality and severe morbidity. Secondary outcomes are time to delivery, preterm birth rate before 32, 34 and 37 weeks, days of admission in neonatal intensive care unit, maternal morbidity, maternal admission days for preterm labour and costs. We will assess growth, physical condition and neurodevelopmental outcome of the children at two years of age. Discussion This study will provide evidence for the usefulness and cost-effectiveness of screening for short cervical length at the 18-22 weeks and subsequent progesterone treatment among low risk women. Trial registration Netherlands Trial Register (NTR): NTR207